PERANCANGAN UI/UX PADA APLIKASI VOUCHER BERBASIS WEBSITE MENGGUNAKAN METODE DESIGN THINKING (STUDI KASUS: KLINIK HIDUP BARU) - Abdi Duta Makarios Zega; Penidas Fiodinggo Tanaem (LPPM Universitas Abdurrab, 2026)
Hidup Baru Clinic has adopt the use of vouchers as one of the methods in good selling and services. The requirement about transaction and operational about record sales and redeems encourage the clinic to design an application. Therefore the clinic necessary to design UI/UX based on website that answer the challenges dan users needs. A popular method such as Design Thinking is utilized to discover innovations and creative solutions to solve problems and meet user requirements. This iterative method, produce a prototype of the voucher application which, after being tested using the System Usability Scale (SUS) by 6 main users of the application, achieved an average score of 92.92 out of 100. This result indicate that the designed application falls within grade A, with an adjective rating of “excellent”, and an acceptability range of “acceptable”.